Ecological and geochemical study of land (soils) within urbanized areas of Belarus for the differentiated norming of pollutant content. I. Arsenic and mercury - Lukashev, Oleg V.; Zhukovskaya, Natalia V.; Lukasheva, Natalia G.; Ilyukova, Irina I.; Savchenko, Vladimir V. (Journal of the Belarusian State University. Geography and Geology, 2019)
The article presents the ecological and geochemical research results of As and Hg in soils within urbanized areas of Belarus. 292 soil samples have been analyzed for As and Hg content (of which 148 samples were taken within Minsk, 132 – regional and district centres, and 12 – Berezinsky Biosphere Reserve). Determination of As and Hg total content has been carried out by atomic absorption method. Outside the industrial sites, the territories of enterprises and dumps, a fairly stable average level of As in the humus horizon, determined by natural factors (mainly mineralogical) has been observed. The average content of the element in the soils of the recreational zone for Belarus as a whole is 0.57 mg / kg, in the residential area is 0.48 mg / kg, in the transport zone is 0.64 mg / kg, in the industrial zone is 0.57 mg / kg. The average content of As in the soils of Berezinsky Biosphere Reserve agricultural lands is 0.50 mg / kg. An insignificant accumulation of As in the soils of the transport zone has been revealed (concentration coefficient is 1.2). The minimum median value (about 0.01 mg / kg), close to the world clark, has been established for Berezinsky Biosphere Reserve agricultural lands, the recreational and residential (0.013 mg / kg) zones in general. Median values of Hg content in transport soils (0.036 mg / kg) and industrial zones (0.021 mg / kg), respectively, are 3.6 and 2.1 times higher. The obtained geochemical indicators has been used when developing soil contamination standards.